RANCANG BANGUN APLIKASI DONOR DARAH DARURAT DONORA BERBASIS WEBSITE MENGGUNAKAN LIVEWIRE LARAVEL - Natania, Ignacia Karina (Universitas Multi Data Palembang, 2024)
The shortage of blood supply in Indonesia is caused by three main factors. These include low public awareness, a large number of expired blood bags, and complicated regulations. According to the Directorate General of Health Services, Ministry of Health of the Republic of Indonesia, each country requires a blood supply of at least 2% of its total population. However, as of June 14 2023, UTD PMI Blood Donation units throughout Indonesia only have a blood stock of 77,438 bags. This shortage has serious consequences because it makes it difficult to meet urgent blood needs and endangers patients who need transfusions. To overcome this problem, further investigation is needed regarding the root of the problem. The solution is Donora, a web-based emergency blood donation application. Donora was developed with Laravel's Livewire framework and leverages existing APIs. This application has 10 main features such as authentication, account management, reward points, notifications, blood stock information, emergency blood donation requests, donor authentication, points ranking, dashboard, etc. Application development follows a SCRUM approach with 5 sprint iterations to ensure efficient development to meet user needs. Application testing was carried out manually using the black box method, and the evaluation results showed that Donora successfully passed all testing stages and demonstrated optimal performance.